2010
DOI: 10.1590/2175-7860201061409
|View full text |Cite
|
Sign up to set email alerts
|

Exotic tree Artocarpus heterophyllus (Moraceae) invades the Brazilian Atlantic Rainforest

Abstract: Artocarpus heterophyllus Lam. (jackfruit) was man made introduced in Tijuca National Park (TNP) in the mid1800s. Native from Southeast Asia, nowadays densely colonizes the TNP. Here we analyze some jackfruit population parameters that probably allowed the local colonization followed by successful invasion of the new habitat. Based on 20 sample plots, randomly placed inside 5 sites colonized by jackfruit, we described subpopulations hierarchical size diameter structures. Gini's coefficient values turned around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 48 publications
0
26
0
14
Order By: Relevance
“…Rondón (2003) (Abreu & Rodrigues 2010). Dentre as espécies citadas, a muanza (A. polycephala) merece destaque, pois, de acordo com as referências consultadas (Cascudo 1964;Caruso 2004), apenas no nosso estudo ela foi citada, e substitui perfeitamente o pau-de-jangada (A. tibourbou).…”
Section: Bancounclassified
“…Rondón (2003) (Abreu & Rodrigues 2010). Dentre as espécies citadas, a muanza (A. polycephala) merece destaque, pois, de acordo com as referências consultadas (Cascudo 1964;Caruso 2004), apenas no nosso estudo ela foi citada, e substitui perfeitamente o pau-de-jangada (A. tibourbou).…”
Section: Bancounclassified
“…Although jackfruit dispersal is predominantly barochoric in the Atlantic forest leading to high rates of seed clumping below the mother-tree (Abreu & Rodrigues, 2010) we observed that sinzoochory by mammals also occurred. This result corroborates the findings of Novelli et al (2010) who performed experiments on barochoric dispersal of A. heterophyllus on sloping terrain.…”
Section: Discussionmentioning
confidence: 65%
“…Our results do not agree with previous studies such as Pizo & Vieira (2004), who found predation rates of native Euterpe edulis palms by generalist rodents not to be dependent on plant density. However, we believe that because jackfruit trees occur in high density (Abreu & Rodrigues, 2010;Bergallo et al 2016), and because the fruit is one of the largest of all tree species (Elevitch & Manner, 2006) the number of fruits and consequently seed availability surpass mammal consumption capacity during more intense fruit production periods. This is corroborated by the fact that adult jackfruit density was high in the three grids and seed predation was low during more intense fruit production periods.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…& Drude (Dislich et al 2002) and Artocarpus heterophyllus Lam. (Abreu & Rodrigues 2010) (Medeiros & Focht 2007). High priority should be given in public policies for these species, in the mentioned ecological regions.…”
Section: Introductionmentioning
confidence: 99%